Current Insights and Future Prospects for Targeting IL-17 to Treat Patients With Systemic Lupus Erythematosus - Koga, Tomohiro; Ichinose, Kunihiro; Kawakami, Atsushi; Tsokos, George C. (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by immune cell abnormalities which lead to the production of autoantibodies and the deposition of immune complexes. Interleukin (IL)-17-producing cells play an important role in the pathogenesis of the disease, making them an attractive therapeutic target. Studies in lupus-prone mice and of ex vivo cells from patients with SLE humans have shown that IL-17 represents a promising therapeutic target. Here we review molecular mechanisms involved in IL-17 production and Th17 cell differentiation and function and an update on the role of IL-17 in autoimmune diseases and the expected usefulness for targeting IL-17 therapeutically.